1990
DOI: 10.1042/bj2710415
|View full text |Cite
|
Sign up to set email alerts
|

cDNA structure and expression of calpactin, a peptide involved in Ca2+-dependent cell aggregation in sponges

Abstract: Aggregation of cells of the marine sponge Geodia cydonium is mediated by an aggregation factor (AF) particle of Mr 1.3 X 10(8). It is now reported that the AF particle is associated with calpactin, which was ascribed a role in the cell-adhesion process. In order to identify the sequence similarity to other members of the lipocortin family, the cDNA of sponge calpactin was cloned and found to display an 80% sequence similarity to vertebrate calpactin II but only a 47% similarity to calpactin I. The calpactin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Compared to BSH diet, our study showed that LFHCC n ‐3 diet reduces Anxa2 expression after 12 wk of dietary intervention. Anxa2 is a multifunctional protein that has been shown to play a major role in membrane‐trafficking events, including exocytosis , endocitosis, and cell adhesion . To be more specific, Anxa2 facilitates the transport of cholesterol ester from caveolae to internal membranes and appears to be involved in GLUT4 translocation in a way that has not been fully defined yet .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to BSH diet, our study showed that LFHCC n ‐3 diet reduces Anxa2 expression after 12 wk of dietary intervention. Anxa2 is a multifunctional protein that has been shown to play a major role in membrane‐trafficking events, including exocytosis , endocitosis, and cell adhesion . To be more specific, Anxa2 facilitates the transport of cholesterol ester from caveolae to internal membranes and appears to be involved in GLUT4 translocation in a way that has not been fully defined yet .…”
Section: Discussionmentioning
confidence: 99%
“…A sponge 68-kDa protein also bound to CS and HA [122]. The AF from G. cydonium is tightly associated with glycosyltransferases [131,132], lectins [88,133,134], and a series of different glycoproteins [121,135]. Polyclonal antibodies raised against purified AF from G. cydonium inhibited cell aggregation of homologous cells but not of heterologous Tethya lyncurium cells CMLS, Cell.…”
Section: General Structure Of Afsmentioning
confidence: 99%
“…protein components. The complexity of sponge cell aggregation is suggested by the finding of many proteins associated with the aggregation factor, among them sialyltransferases (Mü ller et al, 1977), protein kinase C (Gramzow et al, 1988b), calpactin (Robitzki et al, 1990), and other bridge proteins that seem to link the factor to the cell membrane receptors (Gramzow et al, 1986;Varner, 1995). Nevertheless, the nature of the main protein component of the aggregation factor core structure has remained elusive.…”
mentioning
confidence: 99%